Muscle Adaptations to Cardiovascular, Lactate, ATP-PC, and Power Training: Exploring the Principle of Myoplasticity - Christopher K. Carroll (Medical Science: Trends and Innovations Vol. 9, 2025)
Aims: This chapter explores the physiological and physical adaptations of skeletal muscle in response to different exercise modalities, including cardiovascular training, lactate training, adenosine triphosphate-phosphocreatine (ATP-PC) training, and power training. Methodology: A search was conducted on the wide body of research that exists in and around the skeletal muscle and sports performance and aligns the research in a clear manner. Grounded in the Principle of Myoplasticity, the discussion exemplifies how muscle fibers, capillary supply, myoglobin content, mitochondrial function, oxidative enzymes, and energy sources adapt to aerobic training modalities. Results: This chapter works to clarify the role of lactate training in enhancing lactate tolerance and clearance mechanisms. Additionally, ATP-PC training primarily drives neuromuscular adaptations such as improved motor unit recruitment, synchronization, and muscle hypertrophy, contributing to increased force production. A comparable response in power training emphasizes neural efficiency and the stretch-shortening cycle, enhancing rapid force generation and muscle contractile speed. Collaboratively, these adaptations highlight the remarkable plasticity of skeletal muscle in response to varied training stimuli, demonstrating how different exercise regimens uniquely influence muscular performance and endurance. Conclusion: The plasticity of muscle is highly contingent on the stress placed upon it and the adaptations are extensively different.